DESIGN OF CASH FLOW REPORT INFORMATION SYSTEM IN PT. MEDIS KOMPLET INDONESIA - Ruyani (Penelitian dan Pengembangan Ilmu, 2024)
The purpose of writing this final project is to find out how to process cash flow data at PT. Complete Medical Indonesia using a computerized system. Build a computerized system to replace the existing system so that the company can take a quick and appropriate decision so that the company will grow. The information system that will be built in writing this final project is a spare part inventory information system, which can process data that will be stored in the database. The programs used in writing this final project are Visual Basic, and phpMyAdmin. The results of the system built are expected to be able to provide solutions or solutions to existing problems, with existing solutions meaning adding new knowledge that is poured into writing which can be useful for the readers.